Phenomenon of conservatism - Jokūbaitis, Alvydas (Politologija, 1997)
The phenomenon of political thought of conservatism is being dealt with in the article within the context of currently prevailing in social and political sciences discussions about the end of traditional political ideologies. The article is aimed at proving that the conservatism which hardly fits into the framework of the ideologized political thought of the 19th century is currently becoming one of the main factors shaping the new paradigm of political thinking. This idea is based on the conception of conservatism as proposed by the two authors - Edmund Burke and Michael Oakeshott. Burke's merits are identified with his criticism of political rationalism and radicalism, whereas M. Oakeshott was the first to prove that the identity of political thought of conservatism is created not by the specific collection of political principles but rather by a certain perspective of the attitude towards social reality.At the end of the 18th and beginning of the 19th century, a paradigm of ideologized political thinking was formulated. An ideological dogma became more significant than the traditions of political behaviour which were established over a long period of time. Political thinking was dominated by numerous ideological narratives. Conservatism was the only narrative which did not fit into the framework of the paradigm of ideologized political thinking. Ideological political thinking has to a greater extent influenced liberalism and socialism. No doubt, one can identify ideological forms of conservative thinking. However, these forms do not create the phenomenon of conservatism. The unique nature of British conservatism is clearly demonstrated by the opposition to the domination of ideologies in the sphere of political thinking.
Keywords: -